Effect of Laser Irradiance and Fluoride Varnish on Demineralization around Dental Composite Restorations - Valizadeh, Sara; Rahimi Khub, Maryam; Chiniforush, Nasim; Kharazifard, Mohammad-Javad; Hashemikamangar, Sedighe Sadat (Journal of Lasers in Medical Sciences, 2020)
Introduction: This study aimed to assess the effects of CO2 and erbium-doped yttrium aluminum garnet (Er:YAG) lasers with and without fluoride varnish on demineralization around composite restorations. Methods: This in vitro experimental study evaluated 96 extracted human premolars. After preparation and restoration of class V cavities in the buccal surface of the teeth with composite resin, they were randomly divided into 8 groups of control, CO2 laser (L1), CO2 laser-NaF (L1F), NaF-CO2 laser (FL1), Er:YAG laser (L2), Er:YAG laser-NaF (L2F), NaF-Er:YAG laser (FL2) and NaF (F). The entire surface of the teeth, except for the restored cavity in the buccal surface and 1 mm around the margin, was coated with two layers of nail varnish. The teeth then underwent pH cycling for 10 days (3 hours in demineralizing solution and 21 hours in remineralizing solution) to artificially induce demineralization. The amount of calcium and phosphorous released into the cariogenic solution was quantified using atomic absorption spectroscopy and spectrophotometry. The Vickers hardness tester was used to measure the hardness of the tooth structure adjacent to composite restoration. Data were analyzed using one-way ANOVA and Tukey’s test. Results: The four groups of L1F, FL1, FL2 and L2F showed minimum loss of calcium and phosphorous ions, and the mean hardness of FL1 and FL2 groups was higher than that of other groups. Conclusion: The CO2 and Er:YAG lasers alone have no significant effect on the resistance of tooth structure to cariogenic solution. However, they can exert a synergistic effect when used along with NaF varnish. Fluoride varnish applied prior to laser irradiation confers further resistance to the tooth structure and positively affects its hardness.